Afterlife before genesis an introduction: accessing the eternal through Australian Aboriginal music - Turner, David H. (Toronto studies in religion, 1997)
This music is a complex polyphonic interplay of didjereedoo (their hollow log instrument) and voice which not only transcends but also heals. This the author documents by recounting how he learned to play the didjereedoo